Spinal cord stimulation for treatment of failed back surgery syndrome--two case reports - Vijayan, R.; Ahmad, Tunku Sara (Malaysian Medical Association, 1999)
Severe, persistent back pain following back surgery is often referred to as Failed Back Surgery Syndrome (FBSS). Conservative measures such as physiotherapy, back strengthening exercises, transcutaneous electrical nerve stimulation and epidural steroids may be inadequate to alleviate pain. Spinal Cord Stimulators were implanted into two patients suffering from FBSS. Both patients responded successfully to spinal cord stimulation with reduction of pain and disability.